2017
DOI: 10.1080/1331677x.2017.1305799
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing growth and welfare through debt-financed education

Abstract: Using an overlapping generations (OLG) model, we show how relatively small open economies can enhance their growth through educational subsidies financed via public debt and reduce their fertility rate. We show that subsidising education through public debt leads to an A-Pareto improvement of all generations. Even if a country is a net borrower in the international capital market, we show that this subsidy policy can help, under certain conditions, to improve its net borrowing position. This has strong implica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
(45 reference statements)
0
8
0
Order By: Relevance
“…However, this would additionally require an intertemporal redistribution of income from the young to the old as proposed by Boldrin and Montes (2005) and recently by Stauvermann and Kumar (2017). Further, we have shown that the more unequal the distribution of human capital, the higher will be the degree of redistribution of income and the growth rate of the economy.…”
Section: Discussionmentioning
confidence: 93%
“…However, this would additionally require an intertemporal redistribution of income from the young to the old as proposed by Boldrin and Montes (2005) and recently by Stauvermann and Kumar (2017). Further, we have shown that the more unequal the distribution of human capital, the higher will be the degree of redistribution of income and the growth rate of the economy.…”
Section: Discussionmentioning
confidence: 93%
“…We apply an extended Diamond [28] OLG model similar to Stauvermann and Kumar [29][30][31]. The underlying idea goes back to de la Croix and Doepke [33,34].…”
Section: Worldwide Ghg Emissionsmentioning
confidence: 99%
“…The representative agent derives his/her utility from the consumption in the second and third period , the number of children (their quantity) , and the level of the children's human capital stock (their quality) ℎ . The utility function follows from de la Croix and Doepke [25,26,40] and Stauvermann and Kumar [29][30][31].…”
Section: The Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…We apply an extended Diamond [42] overlapping generation (OLG) model [43][44][45][46]. The OLG model has the advantage that it does not rely on the strong assumption of perfect altruism as assumed by Shi and Zhang's [47] model.…”
Section: Introductionmentioning
confidence: 99%